2012
DOI: 10.1021/jz3006805
|View full text |Cite
|
Sign up to set email alerts
|

Calculating the Lifetimes of Metastable States with Complex Density Functional Theory

Abstract: Among other applications, complex absorbing potentials (CAPs) have proven to be useful tools in the theory of metastable states. They facilitate the conversion of unbound states of a finite lifetime into normalized bound states with a complex energy. Adding CAPs to a conventional Hamiltonian turns it into a non-Hermitian operator. Recently, we introduced a complex density functional theory (CODFT) that extends the Kohn-Sham method to the realm of non-Hermitian systems. Here, we combine CAPs with CODFT and pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 37 publications
0
57
0
Order By: Relevance
“…24 Preliminary benchmarks illustrated that this approach results in a computationally more robust scheme in which the dependence on the onset of the CAP is significantly reduced compared to the straightforward application of a CAP along with the original energybased criterion for finding the optimal η, as was done in most CAP applications. [25][26][27] We note that Moiseyev et al 28,29 also observed a linear energy dependence on η beyond some critical value of η and proposed the use of Padé approximants to extrapolate the energy of the stabilized resonance to the zero η limit. If the energy depends strictly linearly on η, their approach yields results identical to our first-order correction.…”
Section: Introductionmentioning
confidence: 78%
“…24 Preliminary benchmarks illustrated that this approach results in a computationally more robust scheme in which the dependence on the onset of the CAP is significantly reduced compared to the straightforward application of a CAP along with the original energybased criterion for finding the optimal η, as was done in most CAP applications. [25][26][27] We note that Moiseyev et al 28,29 also observed a linear energy dependence on η beyond some critical value of η and proposed the use of Padé approximants to extrapolate the energy of the stabilized resonance to the zero η limit. If the energy depends strictly linearly on η, their approach yields results identical to our first-order correction.…”
Section: Introductionmentioning
confidence: 78%
“…In Table III we have listed theoretical results obtained by other workers. Our current results with our best basis set (14s14p5d) are quite far from complex CI [39] and density functional theory (DFT) combined with a CAP [42] calculations. We note that the CI calculations did not include any effect of quadruple excitations.…”
Section: Resultsmentioning
confidence: 68%
“…19,42 Complex scaling and CAP techniques have been applied to several ab initio methods. Complex-scaled and CAP Hartree-Fock (HF) 43,44 and density functional theory (DFT) 45 methods have been introduced; these approaches are only applicable for metastable ground electronic states. Complexscaled configuration-interaction (CI) 43 and multiconfigurational self-consistent field (MCSCF) 44 were successfully used to study resonances in atoms and small molecules, e.g., He, H 2 , Be − .…”
Section: Introductionmentioning
confidence: 99%